Strontium isotope stratigraphy and trace-metal geochemistry of the Ediacaran-Cambrian Bambuí Group, São Francisco Basin - Guacaneme Mora, Cristhian Camilo (2021)
The geological evolution of the intracratonic São Francisco basin in the interior of Gondwana megacontinent is marked by periods of connection and isolation from the global ocean at the end of the Ediacaran and the beginning of the Cambrian. This work provides new aspects on the stratigraphic evolution of the basin based on the detailed trace-metal geochemistry (Cd, Cu, Co, Cr, Mo, Ni, U, V and Zn) and on the Sr-isotope chemostratigraphy of carbonate rocks from the basal Bambuí Group, which potentially record important paleoenvironmental changes in the context of a foreland basin. In the basal 2nd-order regressive sequence, the normalized trace metal data show a progressive increase in the enrichment factor relative to PAAS (Post-Archean Australian Shale), accompanied by a large increase in Sr/Ca ratios (from 0.001 to 0.004) and a decrease in 87Sr/86Sr from 0.7086 to 0.7076. These changes precede a large positive 13C excursion (up to +16) typically found in the middle part of the Bambuí Group, comprised the upper Sete Lagoas and Lagoa do Jacaré formations. The enrichment patterns of trace-metal along this sequence suggests chemical evolution of bottom waters with long residence times and whose redox conditions progressively change from suboxic-anoxic to anoxic-euxinic. Variations in the 87Sr/86Sr ratios indicate that the basin evolved from a seaway connected to the global ocean to a restricted sea, resulted by paleogeographic changes induced by the evolution of marginal Neorproterozic orogenic systems, and changes in the balance between carbonate production and accommodation associated with flexural subsidence, altering the strontium flux and the isotopic compositions of epicontinental seawater. Under conditions of marine restriction, the biochemical characteristics of the deep watermass of the Bambuí sea became extremely sulphidic, with no renewal of oxygenated water, with a scarcity of trace metals transported by upwelling, and with limited fixation of micronutrients. This would have limited nitrogen bioavailability, triggering a challenge for the colonization of the first benthic metazoans in the epicontinental seas of Gondwana in the Ediacaran-Cambrian transition.